The ten rules of Sam Walton : - Bergdahl, Michael (John Wiley & Sonc, 2006)
Praise for The 10 Rules Of Sam Walton "The 10 Rules of Sam Walton is one of those books that should be read and regularly reread by... everyone-business-people, students, teachers, parents, and children